2020
DOI: 10.1007/s12144-020-01068-6
|View full text |Cite
|
Sign up to set email alerts
|

Validity test of the theory of planned behavior in college students’ withdrawal from smartphone dependence

Abstract: Smartphone usage has brought great convenience to our daily life. However, the detrimental consequences of smartphone dependence also require special attention. Based on the theory of planned behavior (TPB), this study designed a questionnaire to investigate college students’ withdrawal from smartphone dependence. The reliability and validity of the questionnaire were tested. The results showed that the reliability of the questionnaire was good (α = 0.84–0.94). The principal component analysis was conducted, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Consumers' environmental concern can be explained as "the degree to which consumers are concerned about environmental problems and support efforts to solve them", for instance by purchasing green or sustainable products (Dunlap and Jones, 2002, p. 485). According to Yue et al (2020), environmental concern can be divided into two categories, such as environmental concern for (1) specific environmental issues (e.g., soil pollution) and (2) comprehensive and universal (e.g., variety of different environmental issues). In this study, we adopted the latter definition, as a full and universal perspective of environmental issues.…”
Section: Environmental Concernmentioning
confidence: 99%
“…Consumers' environmental concern can be explained as "the degree to which consumers are concerned about environmental problems and support efforts to solve them", for instance by purchasing green or sustainable products (Dunlap and Jones, 2002, p. 485). According to Yue et al (2020), environmental concern can be divided into two categories, such as environmental concern for (1) specific environmental issues (e.g., soil pollution) and (2) comprehensive and universal (e.g., variety of different environmental issues). In this study, we adopted the latter definition, as a full and universal perspective of environmental issues.…”
Section: Environmental Concernmentioning
confidence: 99%
“…45 The TPB is used effectively in many areas of health psychology and public health, including to improve vaccination and smoking cessation interventions, 46,47 as a patient's intentions are key to behavior change motivation and effort. There are some reported limitations of the TPB, such as validity concerns with using a patient's intention to predict behavior; 48,49 as there is not a TPB questionnaire, nor a standardized TPB measure (ie researchers develop their own tools). Another limitation of the TPB is the implied cause-effect relationship between behavioral intention and change behavior.…”
Section: Theories Of Planned Behavior and Reasoned Actionmentioning
confidence: 99%
“…Consumer environmental concern is described as "the degree to which consumers care about environmental problems and support efforts to solve them", by purchasing environmentally friendly or sustainable products (Dunlap & Jones, 2002). Based on study by (Yue et al, 2022) environmental concern can be divided into two categories, such as environmental concern for (1) specific environmental issues such as soil pollution and (2) comprehensive and universal, for example: variety of different environmental issues.…”
Section: Environmental Concernmentioning
confidence: 99%
“…Existing literature suggests that environmental concerns are a key factor influencing consumer decision-making processes regarding sustainable products (Diamantopoulos et al, 2003;Sharma & Foropon, 2019) In fact, environmental concerns are often seen as a key indicator of consumer environmental behaviour that directly influencing purchase intentions (Bamberg, 2003;Felix et al, 2018;Hartmann & Apaolaza-Ibáñez, 2012;Santos et al, 2021;Siraj et al, 2022;White & Simpson, 2013;Yue et al, 2022) The study by Testa et al (2020) showed that environmental concern might positively influence the purchase of sustainable packaging as green consumers actively search for environmental information. Park & Lin (2020) indicated that environmental concern has a positive impact on the intention to purchase recycled and upcycled fashion products.…”
Section: Environmental Concernmentioning
confidence: 99%